Presidios of Spanish West Florida - Bense, Judith Ann (Ripley P. Bullen series., 2022)
"This book provides the first comprehensive synthesis of historical and archaeological investigations conducted at the fortified settlements built by Spain in the Florida panhandle from 1698 to 1763"--